Risk Analysis of Job Stress Among Balinese Crew of Cruise Ships - Kusuma, Made Adhyatma Prawira Natha; Susilowati, Indri Hapsari Hapsari (UI Scholars Hub, 2020)
Job stress can appear in all fields of work. Job stress not only occurs from the environment at work but also can be caused by the psychological condition of the workers. Working on a cruise ship demands higher patience to serve the guests in various activities and handle complaints. Moreover, work on cruise ships causes the workers separated from their families for a long time period, which can increase their mental pressure. The aim of this research is to describe the job stress of workers at a cruise ship. This research was conducted in January-June 2017. In an attempt to examine and understand this research, the researcher used a quantitative research method with a cross-sectional design and descriptive approach. The sample of this research was 111 participants with an affordable population are crew members who only come from Bali Province. Researchers used a convenient sampling technique and questionnaire as research instruments. The result shows that 60,36% of respondents experience job stress in moderate categories and 12.61% in the higher categories. The proportion of job stress in the higher categories was: mostly male (16.67%); at galley station (20.00%); working >5 years (14.71%); age group 11-20 years (25.00%); duration of work >11 hours (16.07%); and the level of fatigue is very tired (100%). The data, bivariate analyzed by using Kendall's tau-b correlation test with significance level is 0.05, showed a significant correlation between job stress and fatigue level (p = 0.001, r=0,41). Recommendation to solve these problems are: First, workers need to conduct stress management to minimize the impact of job stress. Second, companies need to pay attention to the workload and complaints of workers so it can develop a sustainable plan, particularly related to job stress.